525 Paediatric Moyamoya Syndrome Associated with Iron Deficiency Anaemia: A Case Report and Review of the Literature. (October 2012) - McElroy, K; Kennedy, A; Houliston, L; Judkins, A; Chaney, G; Richmond, P
Abstract : Introduction: Moyamoya syndrome is a rare, progressive disorder characterised by stenosis of the vasculature of the Circle of Willis with formation of a tortuous collateral system. The aetiology may be idiopathic, or as a consequence of a number of associated diseases. No previous cases secondary to iron-deficiency anaemia have been reported. Aim: To report a case of Moyamoya syndrome secondary to iron-deficiency anaemia, and review the literature with regard to the haematological associations of Moyamoya syndrome. Method: The relevant case notes were reviewed. Key databases were searched for studies including the target phrases "Moyamoya syndrome" and "anaemia". Results: Case history: A 3 year old girl presents with a 12 hour history of right upper limb weakness and slurred speech. A background of pallor, daily vomiting and abdominal pain is elicited. Reduced power in the right upper and lower limbs and a right-sided upgoing plantar are noted on examination. Investigations reveal a haemoglobin of 1.9g/dL, with an iron-deficiency pattern. A faecal occult blood test is positive. Magnetic Resonance (MR) imaging shows focal middle cerebral artery territory ischaemia. MR Angiography shows Moyamoya vessels. Extensive investigations for associated pathologies are normal. Literature review: Sickle cell disease is the most common haematological cause of the Moyamoya syndrome, whilst thalassemia, Fanconi's anaemia and paroxysmal nocturnal haemoglobinuria are also reported. The likely pathogenesis in these instances is intimal proliferation in response to impaired arterial flow. Conclusion: We propose that severe iron-deficiency anaemia may result in Moyamoya syndrome through the mechanism of disrupted intracerebral arterial flow.